MODEL SECRET AGENT OF KINDNESS: INOVASI PEMBELAJARAN AKHLAK MELALUI MISI RAHASIA BERBUAT BAIK DI LINGKUNGAN SEKOLAH - Irna Nur Solikah; Muhammad Syauqi Mubarok (IEC: Journal of Educational Innovation, 2025)
Moral education in schools often emphasizes cognitive understanding of values while overlooking students’ lived moral experiences. This study aims to examine the implementation and impact of the Secret Agent of Kindness model as an innovative approach to moral learning through secret missions of prosocial behavior in the school environment. Employing a qualitative case study design, data were collected through participant observation, in-depth interviews, and documentation involving students and teachers engaged in the model’s implementation. The findings indicate that the Secret Agent of Kindness model fosters students’ intrinsic motivation to perform moral actions, enhances empathy, and strengthens prosocial behavior without reliance on external rewards or supervision. Students demonstrated increased moral awareness, sincerity, and reflective thinking through secret acts of kindness conducted in authentic contexts. The discussion reveals that experiential and reflective moral practices play a crucial role in internalizing moral values. This study concludes that the Secret Agent of Kindness model offers a promising pedagogical alternative for strengthening moral education by bridging the gap between moral knowledge and real-life moral behavior in schools.